Carbon Nanomaterials for the Adsorptive Desulfurization of Fuels. (3rd February 2019) - Svinterikos, Efstratios; Zuburtikudis, Ioannis; Al-Marzouqi, Mohamed
Abstract : The increasing demand for cleaner fuels and the recent stringent regulations of commercial fuel specifications have driven the research of alternative methods to upgrade the current industrial desulfurization technology. Adsorptive desulfurization, the removal of refractory sulfur compounds using appropriate selective tailor-made adsorbents, has shown up as a promising alternative in the recent years. Carbon nanomaterials, namely, graphene, graphene oxide, carbon nanotubes and carbon nanofibers, show a significant potential as desulfurization adsorbents. Their surface area and porosity, their ability of easy functionalization, and their suitability to serve as a support of different types of adsorbents have rendered them attractive candidates for this purpose. In this review, after a presentation of the current industrial desulfurization practice and its limitations, the structure and properties of the carbon nanomaterials of interest will be described, followed by a detailed account of their applications in adsorptive desulfurization. The major literature findings and conclusions will be presented and discussed as a road map for future research in the field.